Antibiotic resistance threats in patients with indwelling urinary catheters: bacterial spectrum, infection rates and the emergence of multidrug resistant and extensively drug resistant strains - Potic, Milan B.; Skakić, Aleksandar; Djordjević, Miodrag (Acta medicae Medianae, 2020)
The extent of antimicrobial resistance has become a global threat and according to the World Health Organization latest reports on this issue 21stcentury could mark the end of the antibiotic era. Catheter-associated urinary tract infections are the leading cause of healthcare-associatedbacteremia and a major source of resistant gram-negativeorganisms. This paper focuses on antibacterial resistance of bacterial species isolated from the urine samples of bacteriuric patients. In this studywe examined urine cultures of patients with indwelling urethral catheters hospitalized for operative treatment and at higher risk for the emergence of hard to eradicate pathogens. We assessed underlying primary health conditions, comorbidities and infection risk factors in an attempt to relate them with rates of resistance. The results of susceptibility testing among positive urine isolates revealed high rates of resistanceto b-lactamase inhibitors, third-generation cephalosporins, fluoroquinolones andtrimethoprim-sulfamethoxazolealongside with combined resistance to third-generation cephalosporins, fluoroquinolones andaminoglycosides. Multi-drug resistant strains were isolated regardless of clinically apparent symptoms and signs of the infection with catheterization duration being the dominant factor in comparison to the severity of primary disease and comorbidities. Administration of empirical therapy failed to address resistance patterns of detected pathogens. The antimicrobial resistance crisis is aggravating and requires prompt and decisive response. Catheterization due to strictly defined indications, reduction of catheter presence duration and choice of therapeutic agent in accordance with susceptibilitytesting are currently best available strategies both for prevention and therapy.
Keywords: Urinary tract infection, Indwelling urethral catheter, Health-care acquired infection, Multi-drug resistance, Extended drug resistance